DIVERSITY OF MICROBES IN SOIL AGGREGATE FRACTIONS UNDER DIFFERENT LAND-USE IN NORTHERN GUINEA SAVANNA, NIGERIA - Lawal, Halima Mohammed; Salifu, U. M.; Amapu, I. Y.; Atta, H. I. (FUDMA JOURNAL OF SCIENCES, 2020)
Microorganisms play vital role in keeping soil healthy. Bacteria, Fungi and Actinobacteria are active in degrading soil organic matter which improves soil ecosystem functioning. There exists a dearth of information on the influence of land-use on diversity of microbes in different soil aggregate sizes in Northern Guinea Savanna of Nigeria. This study assessed the diversity of soil microbes under six different land-use practices namely forest, fallow, pasture legume, pasture cereal, date palm plantation and continuous cultivated. In each land-use soil samples were collected at two depths (0-5 cm and 5-20 cm). The soil samples were divided into two parts, one part was left as collected from the field sites (bulk soil) and the other part was separated into three aggregate fractions (>250 Âµm, >53 Âµm and
Keywords: Soil aggregate fractions, microbes, land-use, diversity and population